Management of Drinking Water Supply System: Authority of Regional Government and Legality of Management by Business Entities - Sesung, Rusdianto; Hadi, Syofyan; Riqiey, Baharuddin (Faculty of Law, Universitas Pekalongan, 2024)
Private water resource control generally tends to follow capitalist and liberal market mechanisms which will result in a large consumer burden. If it follows capitalist and liberal market mechanisms, then what happens is profit oriented compared to fulfilling the needs and prosperity of the community or many people. Based on these problems, this study focuses on the Authority of Regional Governments in managing the Drinking Water Supply System. This study is a legal study using a legislative and conceptual approach. The results of this study indicate that Regional Governments have the authority to manage the Drinking Water Supply System. This is none other than because of the form of state control over water as regulated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia by forming a BUMD or UPTD. In addition, if an area does not yet have drinking water services by a BUMD or UPTD, the implementation of SPAM by the business entity is legally valid. Conversely, if an area already has drinking water services by a BUMD or UPTD, the implementation of SPAM by the business entity is not legally valid.